Leveraging Technology towards HR Excellence - M., Dileep Kumar. (Information Management and Business Review, 2012)
The last decade has seen a significant increase in the number of organizations gathering, storing and analyzing human resources data using Human Resource Information Systems (HRIS) (Ball, 2001; Barron et al., 2004; Hussain et al., 2007; Ngai & Wat, 2006). HR to benefit almost every realm of business operations is leveraging technology. Many technology applications support Human Resource functions like erecruitment, employee tracking system, performance management software, e earning mode etc are helping dramatically to improve HR’s ability to carry out effective talent management and get better employer brand. Integration of technology and HR not only mean harmonious co-existing but would also mean the journey towards business excellence. This paper explores the understanding on positive impact of Human Resource Information System (HRIS) currently in use for people management with perception on Information Communication Technology (ICT) applications adopted by many industries. The study follows qualitative research as its plan of action in gathering information. The information gathered in crosschecked with industry to cross check the reliability.